Non-electroconductive flux, connected structure, and method for producing connected structure

JP2025032138AInactive Publication Date: 2025-03-11SEKISUI CHEMICAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024202157
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-01-20
Filing Date
2024-11-20
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0020】 本発明に係る非導電性フラックスは、エポキシ化合物と、酸無水物硬化剤と、有機リン化合物とを含む。本発明に係る非導電性フラックスでは、上記の構成が備えられているので、得られる接続構造体の生産性及び耐衝撃性を高め、はんだフラッシュの発生を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032138000001_ABST
    Figure 2025032138000001_ABST
Patent Text Reader

Abstract

To provide a non-electroconductive flux that is capable of enhancing productivity and impact resistance in a connected structure obtained therefrom, while suppressing the occurrence of solder flash.SOLUTION: A non-electroconductive flux according to the present invention contains an epoxy compound, an acid anhydride curing agent, and an organophosphorus compound.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-conductive flux. The present invention also relates to a connection structure using the non-conductive flux and a method for manufacturing the connection structure. [Background technology]

[0002] In recent years, with the miniaturization, weight reduction, and high functionality of electronic devices such as data servers, personal computers (PCs), and mobile terminals, finer pitch wiring is being adopted for printed wiring boards, etc. For this reason, surface mount packages such as ball grid arrays (BGAs), in which the wiring extends directly under the chip, and ultra-small chip scale packages (CSPs) are attracting attention.

[0003] However, in surface mount packages such as BGA, unlike conventional pin insertion packages, the electrodes on the surface of the wiring board are connected to each other by solder balls, which results in poor adhesion and makes them more susceptible to damage when dropped (low impact resistance).

[0004] Therefore, the joint portion may be reinforced by filling the gap between the surface mount package and the wiring board with an underfill material and then curing it.

[0005] The following Patent Document 1 discloses a semiconductor package substrate on one side of which a semiconductor chip is flip-chip mounted. The semiconductor package substrate is mounted on a printed wiring board from the other side of the semiconductor package substrate. The semiconductor package substrate includes a core base material, a build-up layer, and a stress buffer layer. The build-up layer is a multi-layer wiring layer in which wiring patterns and insulating resin layers are alternately laminated, and the uppermost layer of the build-up layer is a wiring pattern. The stress buffer layer is provided on the surface of the build-up layer on the other side. The stress buffer layer includes a first stress buffer layer and a second stress buffer layer on the first stress relaxation layer, and the first stress buffer layer and the second stress buffer layer each include a via and a wiring pattern. After the semiconductor chip is mounted on one side of the semiconductor package substrate, an underfill material is filled between the semiconductor chip and the semiconductor package substrate. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2018-186121 A Summary of the Invention [Problem to be solved by the invention]

[0007] When an underfill material such as that disclosed in Patent Document 1 is used as a sealant, the adhesion between the semiconductor chip and the semiconductor package substrate can be improved, and the impact resistance of the resulting connection structure (semiconductor package) can be improved.

[0008] However, in the manufacturing process of the connection structure, after the reflow process is performed to connect the electrodes, the underfill material must be permeated and filled between the semiconductor chip and the semiconductor package substrate by capillary action, and the reflow process must be performed again to harden the underfill material. That is, in the conventional manufacturing method of the connection structure using the underfill material, the reflow process must be performed twice, which results in low productivity. Furthermore, in the connection structure using the conventional underfill material, the solder connecting the electrodes melts during the second reflow process, which may cause a phenomenon (solder flash) in which the solder advances while destroying the interface between the underfill material and the component (or substrate). When solder flash occurs, a short circuit or open circuit may occur.

[0009] An object of the present invention is to provide a non-conductive flux capable of increasing the productivity and impact resistance of the resulting connection structure and suppressing the occurrence of solder flash. Another object of the present invention is to provide a connection structure using the non-conductive flux and a method for manufacturing the connection structure. [Means for solving the problem]

[0010] According to a broad aspect of the present invention, there is provided a non-conductive flux that includes an epoxy compound, an acid anhydride curing agent, and an organophosphorus compound.

[0011] In a specific aspect of the non-conductive flux according to the present invention, the adhesive strength at 25° C. is 100,000 N / m 2 More than 210000N / m 2 The following is the result.

[0012] In a specific aspect of the non-conductive flux according to the present invention, the viscosity at 25° C. is 400 Pa·s or less.

[0013] In a specific aspect of the non-conductive flux according to the present invention, the viscosity at 25° C. is 50 Pa·s or less.

[0014] In a specific aspect of the non-conductive flux according to the present invention, the content of the organophosphorus compound is 0.5 parts by weight or more and 10 parts by weight or less with respect to 100 parts by weight of the acid anhydride curing agent.

[0015] In a specific aspect of the non-conductive flux according to the present invention, the content of the acid anhydride curing agent is 5% by weight or more and 50% by weight or less, based on 100% by weight of the non-conductive flux.

[0016] In a specific aspect of the non-conductive flux according to the present invention, the non-conductive flux is a paste.

[0017] According to a broad aspect of the present invention, there is provided a connection structure comprising a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a resin part connecting the first connection target member and the second connection target member, wherein the first electrode comprises a first electrode body and solder particles on a surface of the first electrode body, the first electrode body and the second electrode are electrically connected, and the material of the resin part is the non-conductive flux described above.

[0018] According to a broad aspect of the present invention, there is provided a method for manufacturing a connection structure, comprising: a first arrangement step of using a first connection target member having a first electrode on a surface thereof, the first electrode comprising a first electrode body and solder particles on a surface of the first electrode body, and using the above-mentioned non-conductive flux to arrange the non-conductive flux on a surface of the solder particles in the first connection target member; a second arrangement step of arranging the first connection target member on which the non-conductive flux is arranged, and a second connection target member having a second electrode on its surface, such that the first electrode and the second electrode face each other; and a step of heating the solder particles and the non-conductive flux to electrically connect the first electrode and the second electrode, and forming a resin part connecting the first connection target member and the second connection target member using the non-conductive flux.

[0019] In a specific aspect of the method for manufacturing a connection structure according to the present invention, in the first placing step, the non-conductive flux is placed by dipping. Effect of the Invention

[0020] The non-conductive flux according to the present invention contains an epoxy compound, an acid anhydride curing agent, and an organic phosphorus compound. Since the non-conductive flux according to the present invention has the above-mentioned components, it is possible to improve the productivity and impact resistance of the resulting connection structure and to suppress the occurrence of solder flash. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a connection structure obtained by using a non-conductive flux according to one embodiment of the present invention. [Diagram 2] 2(a) to (d) are cross-sectional views illustrating the steps of an example of a method for producing a connection structure using the non-conductive flux according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention will be described in detail below.

[0023] (Non-conductive flux) The non-conductive flux according to the present invention includes an epoxy compound, an acid anhydride curing agent, and an organic phosphorus compound. The non-conductive flux does not have electrical conductivity. The non-conductive flux preferably does not include a conductive material. The non-conductive flux preferably does not include conductive particles. The non-conductive flux preferably does not include solder. The non-conductive flux preferably does not include solder particles. The non-conductive flux is also heat curable. The non-conductive flux has a property of being cured by heating.

[0024] When sealing is performed using an underfill material as in the past, a reflow process must be performed twice for solder bonding and hardening of the underfill material, which poses the problem of low productivity.

[0025] Since the non-conductive flux according to the present invention has the above-mentioned configuration, when a connection structure is produced using the non-conductive flux, the solder can be melted and the electrodes can be connected together in a single reflow process, and the non-conductive flux can be hardened. Therefore, it is not necessary to perform the reflow process twice. In other words, the non-conductive flux according to the present invention allows for simultaneous mounting when producing a connection structure, thereby improving productivity.

[0026] The non-conductive flux according to the present invention may be used by being placed on the surface of the solder particles before the reflow process performed to melt the solder and connect the electrodes. That is, the non-conductive flux according to the present invention may be used as a first-in underfill material. The non-conductive flux according to the present invention is preferably used as a first-in underfill material. In this case, the number of reflow processes can be reduced compared to the case where the underfill material is filled after the reflow process for connecting the electrodes and the reflow process is performed again. That is, when the non-conductive flux according to the present invention is used as a first-in underfill material, the connection structure can be manufactured by mounting the components all at once, and the productivity can be further improved.

[0027] In addition, since the non-conductive flux according to the present invention has the above-mentioned configuration, for example, when disposing the non-conductive flux on a package by dipping, a sufficient amount of the non-conductive flux can be disposed. As a result, when a connection structure using the non-conductive flux according to the present invention is subjected to an impact such as dropping, the probability of the connection structure breaking down due to a connection failure can be reduced. In other words, the impact resistance of the resulting connection structure can be improved. In addition, when disposing the non-conductive flux on the connection target member, the connection target member can be easily pulled up from the dipping tank.

[0028] Furthermore, since the non-conductive flux according to the present invention has the above-mentioned configuration, it is possible to suppress the occurrence of solder flash in the resulting connection structure and to improve the solder flash resistance, and as a result, it is possible to suppress the occurrence of short circuits and open circuit defects in the connection structure using the non-conductive flux according to the present invention.

[0029] Furthermore, since the non-conductive flux according to the present invention has the above-mentioned configuration, the connection resistance between the upper and lower electrodes in the resulting connection structure can be reduced, and as a result, the electrical connection reliability can be improved. In particular, the present invention uses an acid anhydride hardener and an organic phosphorus compound in combination, which can significantly improve the flux effect.

[0030] In the present invention, non-conductive means that the insulation resistance is less than 1.0×10 6 Ω or more. The insulation resistance of the non-conductive flux can be measured, for example, by the following method. A test specimen is obtained by applying a non-conductive flux to a thickness of 100 μm on the surface of a comb-shaped substrate having a copper electrode on its surface. The obtained test specimen is heated to 160° C. at 2° C. / sec in a nitrogen atmosphere (oxygen concentration 100 ppm or less) using a reflow simulator (for example, Core9046a manufactured by Cores Corporation), and then cooled to room temperature (23° C.). A voltage of 5 V is then applied, and the insulation resistance is measured using a measuring device (for example, Electrochemical Migration Evaluation System manufactured by ESPEC Corporation).

[0031] In the present invention, the flux refers to a composition having a solder wettability diameter of 600 μm or more in the following solder wettability test. The composition is applied to a thickness of 150 μm on the surface of a gold-plated printed circuit board, and SnBi solder particles (particle diameter 500 μm, melting point 139° C.) are placed on the surface of the composition to obtain a test specimen. The obtained test specimen is heated to 160° C. at 2° C. / sec in a nitrogen atmosphere (oxygen concentration 100 ppm or less) using a reflow simulator (for example, Core9046a manufactured by Cores Corporation), and is held for 3 minutes, and then cooled to room temperature (23° C.). Thereafter, the shape of the solder that has spread out is approximated by an ellipse, and the average of the minor axis and major axis of the ellipse ((minor axis + major axis) / 2) is taken as the solder wettability diameter of the composition. The above ellipse is a concept that includes a perfect circle, and when the above ellipse is a perfect circle, the solder wettability diameter of the composition is the diameter of the perfect circle.

[0032] The non-conductive flux according to the present invention can be suitably used for connecting a surface mount package to a wiring board. Examples of the surface mount package include BGA and CSP.

[0033] The adhesive strength (tack strength) of the non-conductive flux at 25°C is preferably 50000 N / m 2 More preferably, 100,000N / m 2 More preferably, 120,000 N / m 2 More preferably, 140,000 N / m 2 The adhesive strength (tack strength) of the non-conductive flux at 25° C. is preferably 250,000 N / m 2 Less than or equal to 210,000 N / m 2 or less, more preferably 170,000 N / m 2 Below 160000N / m 2or less. When the adhesive strength of the non-conductive flux at 25°C is equal to or greater than the lower limit, a sufficient amount of the non-conductive flux can be placed on the package by dipping. As a result, the impact resistance of the resulting connection structure can be improved even more effectively. Furthermore, when the adhesive strength of the non-conductive flux at 25°C is equal to or less than the upper limit, the package can be easily removed from the dipping tank.

[0034] The adhesive strength (tack strength) of the non-conductive flux at 25°C is measured as follows. The non-conductive flux is applied to a surface of a stainless steel plate to a thickness of 50 μm to obtain a laminate. Using a tack tester, a probe (diameter 8 mm, 10 g) is pressed into the laminate for 10 seconds, and then the load when the probe is lifted at a speed of 0.1 mm / sec is measured. Examples of tack testers include the "TA-500" manufactured by UBM.

[0035] From the viewpoint of more effectively increasing the impact resistance of the resulting connection structure, the viscosity (η25) of the non-conductive flux at 25°C is preferably 5 Pa·s or more, more preferably 25 Pa·s or more, and preferably 400 Pa·s or less, more preferably 300 Pa·s or less, even more preferably 50 Pa·s or less, and particularly preferably 40 Pa·s or less. The viscosity (η25) can be appropriately adjusted by the types and amounts of the blended components.

[0036] The viscosity (η25) can be measured, for example, using an E-type viscometer ("TVE22L" manufactured by Toki Sangyo Co., Ltd.) under conditions of 25° C. and 10 rpm.

[0037] From the standpoint of improving the impact resistance of the resulting connection structure, the non-conductive flux is preferably in a liquid state at 25° C., and is preferably in the form of a paste.

[0038] From the viewpoint of more effectively increasing the impact resistance of the resulting connection structure, the melting point of the non-conductive flux is preferably 40°C or higher, more preferably 70°C or higher, and preferably 350°C or lower, more preferably 310°C or lower.

[0039] The melting point of the non-conductive flux can be determined by differential scanning calorimetry (DSC). An example of a DSC device is the "EXSTAR DSC7020" manufactured by SII Corporation.

[0040] From the viewpoint of improving the conductivity reliability, the reaction initiation temperature of the non-conductive flux is preferably 50° C. or higher, more preferably 70° C. or higher, even more preferably 80° C. or higher, and is preferably 250° C. or lower, more preferably 200° C. or lower, even more preferably 150° C. or lower, and particularly preferably 140° C. or lower.

[0041] <Epoxy compounds> The epoxy compound is a compound having at least one epoxy group. Examples of the epoxy compound include bixylenol type epoxy compound, bisphenol A type epoxy compound, bisphenol F type epoxy compound, bisphenol S type epoxy compound, phenol novolac type epoxy compound, biphenyl type epoxy compound, biphenyl novolac type epoxy compound, biphenol type epoxy compound, naphthalene type epoxy compound, fluorene type epoxy compound, phenol aralkyl type epoxy compound, naphthol aralkyl type epoxy compound, dicyclopentadiene type epoxy compound, anthracene type epoxy compound, epoxy compound having an adamantane skeleton, epoxy compound having a tricyclodecane skeleton, naphthylene ether type epoxy compound, and epoxy compound having a triazine nucleus in the skeleton. The epoxy compound may be used alone or in combination of two or more.

[0042] From the viewpoint of improving dipping properties, the epoxy compound is preferably a bixylenol type epoxy compound, a bisphenol F type epoxy compound, or an epoxy compound having a triazine nucleus in the skeleton, and more preferably a bixylenol type epoxy compound or a bisphenol F type epoxy compound. The epoxy compound is further preferably a bixylenol type epoxy compound.

[0043] From the viewpoint of further increasing the impact resistance of the resulting connection structure, the epoxy compound is preferably liquid at 25°C.

[0044] From the viewpoint of further enhancing the impact resistance of the resulting connection structure, the content of the epoxy compound in 100% by weight of the non-conductive flux is preferably 15% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, and is preferably 70% by weight or less, more preferably 60% by weight or less, even more preferably 55% by weight or less.

[0045] <Acid anhydride hardener> The acid anhydride curing agent thermally cures the epoxy compound. The acid anhydride curing agent is used in combination with an organic phosphorus compound described below, which significantly enhances the flux effect of the non-conductive flux. As a result, the oxide film on the surface of the electrode and solder in the resulting connection structure can be effectively removed.

[0046] Examples of the acid anhydride hardener include phthalic anhydride, tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylbutenyltetrahydrophthalic anhydride, anhydrides of phthalic acid derivatives, maleic anhydride, nadic anhydride, methylnadic anhydride, glutaric anhydride, succinic anhydride, glycerin bistrimellitic anhydride monoacetate, and ethylene glycol bistrimellitic anhydride, and other bifunctional acid anhydride hardeners, such as trimellitic anhydride, and tetrafunctional or higher acid anhydride hardeners, such as pyromellitic anhydride, benzophenonetetracarboxylic anhydride, methylcyclohexenetetracarboxylic anhydride, and polyazelaic anhydride. Only one of the above acid anhydride hardeners may be used, or two or more of them may be used in combination.

[0047] From the viewpoint of improving dipping properties, the acid anhydride curing agent is preferably tetrahydrophthalic anhydride or hexahydrophthalic anhydride, and more preferably hexahydrophthalic anhydride. From the viewpoint of further improving dipping properties, the hexahydrophthalic anhydride is preferably methylhexahydrophthalic anhydride.

[0048] In 100% by weight of the non-conductive flux, the content of the acid anhydride curing agent is preferably 5% by weight or more, more preferably 10% by weight or more, and even more preferably 25% by weight or more, and is preferably 60% by weight or less, more preferably 50% by weight or less, and even more preferably 45% by weight or less. When the content of the acid anhydride curing agent is equal to or more than the lower limit and equal to or less than the upper limit, the impact resistance and solder flash resistance of the resulting connection structure can be further improved.

[0049] The content of the acid anhydride curing agent is preferably 50 parts by weight or more, more preferably 60 parts by weight or more, even more preferably 70 parts by weight or more, and is preferably 120 parts by weight or less, more preferably 110 parts by weight or less, and even more preferably 100 parts by weight or less, relative to 100 parts by weight of the epoxy compound. When the content of the acid anhydride curing agent is equal to or more than the lower limit and equal to or less than the upper limit, the impact resistance and solder flash resistance of the resulting connection structure can be further improved.

[0050] <Organophosphorus compounds> By using the organic phosphorus compound and the acid anhydride curing agent in combination, the flux property of the non-conductive flux can be improved. As a result, the oxide film on the surface of the electrode and the solder in the resulting connection structure can be effectively removed. In addition, the impact resistance of the resulting connection structure can be improved.

[0051] Examples of the organic phosphorus compound include organic phosphonium salts, organic phosphoric acids, organic phosphoric acid esters, organic phosphonic acids, organic phosphonic acid esters, organic phosphinic acids, and organic phosphinic acid esters. The organic phosphorus compounds may be used alone or in combination of two or more.

[0052] From the viewpoint of improving the conduction reliability, the organophosphonium compound is preferably an organophosphonium salt, an organophosphoric acid, or an organophosphate ester, and more preferably an organophosphonium salt.

[0053] The organic phosphonium salt includes an organic phosphonium salt composed of a phosphonium ion and its counter ion.

[0054] From the viewpoint of improving the conduction reliability, the organic phosphonium salt is preferably methyltributylphosphonium dimethyl phosphate, tributylmethylphosphonium bis(2-ethylhexyl)phosphate, or tetrabutylphosphonium bromide, and more preferably methyltributylphosphonium dimethyl phosphate.

[0055] Commercially available organic phosphonium salts include the "Hishicoline" series manufactured by Nippon Chemical Industry Co., Ltd.

[0056] The organic phosphoric acid, the organic phosphoric acid ester, the organic phosphonic acid, the organic phosphonic acid ester, the organic phosphinic acid, and the organic phosphinic acid ester are not particularly limited, and conventionally known compounds or commercially available products can be used.

[0057] From the viewpoint of further increasing the impact resistance of the resulting connection structure, the above-mentioned organophosphorus compound is preferably liquid at 25°C.

[0058] From the viewpoint of further enhancing the impact resistance and solder flash resistance of the resulting connection structure, the content of the above-mentioned organic phosphorus compound in 100% by weight of the above-mentioned non-conductive flux is preferably 0.5% by weight or more, more preferably 0.8% by weight or more, and is preferably 10% by weight or less, more preferably 8.0% by weight or less, and even more preferably 4.0% by weight or less.

[0059] From the viewpoint of further enhancing the impact resistance and solder flash resistance of the resulting connection structure, the content of the organophosphorus compound is preferably 0.5 parts by weight or more, more preferably 1 part by weight or more, and even more preferably 2 parts by weight or more, relative to 100 parts by weight of the acid anhydride curing agent, and is preferably 10 parts by weight or less, and more preferably 5 parts by weight or less.

[0060] <Other ingredients> The non-conductive flux may contain various additives, such as a filler, an extender, a softener, a plasticizer, a thixotropic agent, a leveling agent, a polymerization catalyst, a curing catalyst, a colorant, an antioxidant, a heat stabilizer, a light stabilizer, an ultraviolet absorber, a lubricant, an antistatic agent, and a flame retardant, as necessary.

[0061] From the viewpoint of further enhancing the flux property, the non-conductive flux may contain a compound having a carboxyl group or may contain a carboxylic acid compound. Since the non-conductive flux has excellent flux property, the non-conductive flux does not need to contain a compound having a carboxyl group or may not contain a carboxylic acid compound.

[0062] (Connection structure and method for manufacturing the connection structure) The non-conductive flux according to the present invention is preferably used to obtain a connection structure. The non-conductive flux according to the present invention is preferably used for application on the surface of a solder (use of the non-conductive flux on the surface of a solder). The non-conductive flux according to the present invention is preferably used for application on the surface of a solder particle (use of the non-conductive flux on the surface of a solder particle). The non-conductive flux according to the present invention may be a coating material for a solder. The non-conductive flux according to the present invention may be a coating material for a solder particle. The non-conductive flux according to the present invention is also preferably used for application on the surface of an electrode (use of the non-conductive flux on the surface of an electrode). The non-conductive flux according to the present invention is also preferably used for application on the surface of a conductive particle (use of the non-conductive flux on the surface of a conductive particle). The non-conductive flux according to the present invention may be a coating material for an electrode. The non-conductive flux according to the present invention may be a coating material for a conductive particle.

[0063] The connection structure according to the present invention comprises a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a resin part connecting the first connection target member and the second connection target member. In the connection structure according to the present invention, the first electrode comprises a first electrode body and solder particles on a surface of the first electrode body. In the connection structure according to the present invention, the first electrode body and the second electrode are electrically connected. In the connection structure according to the present invention, the material of the resin part is the non-conductive flux described above.

[0064] In the method for manufacturing a connection structure according to the present invention, a first connection target member having a first electrode on a surface thereof is used, and the first electrode comprises a first electrode body and solder particles on the surface of the first electrode body. In the method for manufacturing a connection structure according to the present invention, the method includes a first arranging step of using the first connection target member and the non-conductive flux to arrange the non-conductive flux on the surface of the solder particles in the first connection target member. In the method for manufacturing a connection structure according to the present invention, the method includes a second arranging step of arranging the first connection target member on which the non-conductive flux is arranged and a second connection target member having a second electrode on its surface such that the first electrode and the second electrode face each other. In the method for manufacturing a connection structure according to the present invention, the method includes a step of heating the solder particles and the non-conductive flux to electrically connect the first electrode and the second electrode, and forming a resin part connecting the first connection target member and the second connection target member with the non-conductive flux.

[0065] In the method for manufacturing a connection structure according to the present invention, in the first disposing step, the non-conductive flux may be disposed by dispensing, by screen printing, by ejection by an inkjet device, or by dipping. From the viewpoint of further increasing productivity, it is preferable to dispose the non-conductive flux by dipping in the first disposing step.

[0066] In a conventional method for manufacturing a connection structure using an underfill material, after a reflow step for connecting electrodes, the underfill material must be permeated and filled between the components to be connected by capillary action, and a reflow step must be performed again to harden the underfill material. In other words, in a conventional method for manufacturing a connection structure using an underfill material, the reflow step must be performed twice, resulting in low productivity. Furthermore, in a connection structure using a conventional underfill material, solder flash may occur. When solder flash occurs, a short circuit or open circuit may occur.

[0067] In the connection structure and the method for manufacturing the connection structure according to the present invention, a specific non-conductive flux is used, so that the electrodes can be electrically connected to each other and the non-conductive flux can be hardened by one reflow process. Therefore, there is no need to perform the reflow process twice. That is, in the connection structure and the method for manufacturing the connection structure according to the present invention, it is possible to mount the components all at once, and as a result, the productivity can be further improved. In addition, in the connection structure and the method for manufacturing the connection structure according to the present invention, a specific non-conductive flux is used, so that when the non-conductive flux is placed on the package by dipping, for example, a sufficient amount of the flux can be placed. As a result, when the connection structure is subjected to an impact such as a drop, the probability that a connection failure occurs and the connection structure breaks down can be reduced (impact resistance can be increased). Furthermore, in the connection structure and the method for manufacturing the connection structure according to the present invention, a specific non-conductive flux is used, so that the occurrence of solder flash can be suppressed. As a result, the occurrence of short or open defects can be suppressed in the obtained connection structure.

[0068] Hereinafter, specific embodiments of the present invention will be described with reference to the drawings.

[0069] FIG. 1 is a cross-sectional view that illustrates a connection structure obtained by using a non-conductive flux according to one embodiment of the present invention.

[0070] The connection structure 1 shown in FIG. 1 includes a first connection target member 2, a second connection target member 3, and a resin part 4 connecting the first connection target member 2 and the second connection target member 3. The resin part 4 is formed of a non-conductive flux 4Xa (see FIGS. 2(a) to (d)). The material of the resin part 4 is the non-conductive flux 4Xa. In this embodiment, the non-conductive flux 4Xa contains an epoxy compound, an acid anhydride curing agent, and an organic phosphorus compound. In this embodiment, the non-conductive flux 4Xa is a paste.

[0071] The resin portion 4 is a cured portion obtained by thermally curing the non-conductive flux 4Xa.

[0072] The first connection target member 2 has a plurality of first electrodes on its surface (lower surface). The first electrode comprises a first electrode body 2a and a solder portion 2B (solder particles) on the surface of the first electrode body 2a. The first electrode is a composite electrode of the first electrode body 2a and the solder portion 2B. The second connection target member 3 has a plurality of second electrodes 3a on its surface (upper surface). In the connection structure 1, the first electrode body 2a and the second electrode 3a are electrically connected. In the connection structure 1, the first electrode body 2a and the second electrode 3a are electrically connected by the solder portion 2B.

[0073] As shown in FIG. 1, in the connection structure 1, between the first electrode body 2a and the second electrode 3a, at least the portion of the solder particles that contacts the second electrode 3a melts, and then the solder particles solidify to form the solder portion 2B. This increases the connection area between the solder portion 2B and the second electrode 3a. In the connection structure, the solder particles may remain. In the connection structure, the solder particles and the solder portion may be present.

[0074] Next, an example of a method for producing a connection structure will be specifically described with reference to Figures 2(a) to (d). Figures 2(a) to (d) are cross-sectional views for explaining each step of an example of a method for producing a connection structure using a non-conductive flux according to one embodiment of the present invention.

[0075] First, as shown in FIG. 2(a) and FIG. 2(b), a first connection target member 2 having a first electrode on its surface (lower surface) is prepared. The first electrode includes a first electrode body 2a and solder particles 2b on the surface of the first electrode body 2a. In addition, a non-conductive flux 4Xa is prepared. The non-conductive flux 4Xa is filled in a dipping tank 4X. The non-conductive flux 4Xa is placed on the surface of the solder particles 2b of the first connection target member 2 (first placing step). The non-conductive flux 4Xa contains an epoxy compound, an acid anhydride curing agent, and an organic phosphorus compound.

[0076] In a first arrangement step, non-conductive flux 4Xa is arranged on the surfaces of the solder particles 2b in the first connection target member 2 by dipping. The first connection target member 2 is immersed in a dipping tank 4X filled with non-conductive flux 4Xa, and the non-conductive flux 4Xa is arranged on the surfaces of the solder particles 2b in the first connection target member 2. The non-conductive flux 4Xa coats the surfaces of the solder particles 2b and forms a coating layer. The coating layer, which is the non-conductive flux 4Xa, is arranged along the surfaces of the solder particles 2b.

[0077] The amount of non-conductive flux placed on the surface of the solder particles is preferably an amount capable of filling the gap between the first connection target member and the second connection target member in the resulting connection structure.

[0078] Also, a second connection target member 3 having a second electrode 3a on its surface (upper surface) is prepared. Next, as shown in Figs. 2(b) and (c), the first connection target member 2 on which the non-conductive flux 4Xa is disposed and the second connection target member 3 are disposed so that the first electrode (first electrode body 2a and solder particles 2b) faces the second electrode 3a (second disposing step). The second connection target member 3 is disposed from the second electrode 3a side toward the first electrode side of the first connection target member 2. At this time, the first electrode body 2a and the second electrode 3a are disposed to face each other.

[0079] Next, as shown in FIG. 2(d), the solder particles 2b and the non-conductive flux 4Xa are heated (third step). Preferably, the non-conductive flux is heated to a temperature at which the portion of the solder particles in contact with the second electrode melts or higher. More preferably, the non-conductive flux 4Xa is heated to a temperature at which the epoxy compound hardens or higher. This heating electrically connects the first electrode (the first electrode body 2a, and the solder particles 2b or the solder portion 2B) to the second electrode 2a. In addition, the non-conductive flux 4Xa is thermally hardened. As a result, as shown in FIG. 2(d), the resin portion 4 connecting the first connection target member 2 and the second connection target member 3 is formed by the non-conductive flux 4Xa. The resin portion 4 is formed by the thermal hardening of the non-conductive flux 4Xa. In addition, as shown in FIG. 2(d), the solder portion 2B is formed by the solder particles 2b, and the first electrode body 2a and the second electrode 3a are electrically connected by the solder portion 2B.

[0080] In this manner, the connection structure 1 shown in FIG. 1 is obtained. The second step and the third step may be performed consecutively. After the second step, the laminate of the first connection target member 2, the non-conductive flux 4Xa, and the second connection target member 3 may be moved to a heating section and the third step may be performed. To perform the heating, the laminate may be placed on a heating member, or the laminate may be placed in a heated space.

[0081] The heating temperature in the third step is preferably 140°C or higher, more preferably 160°C or higher, and preferably 450°C or lower, more preferably 250°C or lower, and even more preferably 200°C or lower. The heating temperature in the third step is preferably a temperature higher than the melting point of the solder particles. The heating temperature in the third step is preferably a temperature higher than the curing temperature of the epoxy compound. The heating temperature in the third step is preferably a temperature higher than the temperature at which the portion of the solder particles in contact with the second electrode melts, and more preferably a temperature higher than the curing temperature of the epoxy compound.

[0082] The heating method in the third step includes a method of heating the entire laminate using a reflow furnace or an oven, and a method of locally heating only the solder portion (solder particles) and resin portion (non-conductive flux) of the laminate.

[0083] Examples of tools used in the localized heating method include a hot plate, a heat gun that applies hot air, a soldering iron, and an infrared heater.

[0084] In addition, when applying localized heating with a hot plate, it is preferable that the upper surface of the hot plate be made of a metal with high thermal conductivity directly below the solder portion (solder particles) and the resin portion (non-conductive flux), and that other areas where it is not desirable to heat the hot plate be made of a material with low thermal conductivity, such as fluororesin.

[0085] The thickness of the solder portion in the connection structure is preferably 10 μm or more, more preferably 20 μm or more, and is preferably 100 μm or less, more preferably 80 μm or less.

[0086] The thickness of the resin portion in the connection structure is preferably 10 μm or more, more preferably 20 μm or more, and is preferably 100 μm or less, more preferably 80 μm or less.

[0087] The viscosity (ηmp) of the non-conductive flux at the melting point of the solder particles is preferably 0.1 Pa s or more, more preferably 0.2 Pa s or more, and preferably 50 Pa s or less, more preferably 10 Pa s or less, and even more preferably 1 Pa s or less. If the viscosity (ηmp) is equal to or more than the lower limit and equal to or less than the upper limit, the conductivity reliability can be further improved.

[0088] The viscosity (ηmp) can be measured, for example, using a rheometer "HAAKE MARS III" manufactured by Thermo Fisher Scientific under the conditions of a frequency of 2 Hz, a temperature rise rate of 0.11°C / sec, and a measurement temperature range of 25°C to 200°C (however, if the melting point of the solder particles exceeds 200°C, the upper temperature limit is set to the melting point of the solder particles). From the measurement results, the viscosity at the melting point (°C) of the solder particles is evaluated.

[0089] When the non-conductive flux is in the form of a paste (liquid), the thickness of the resin portion can be easily adjusted by changing the amount of non-conductive flux applied.

[0090] The first and second connection target members are not particularly limited. Specific examples of the first and second connection target members include electronic components such as semiconductor chips, semiconductor packages, LED chips, LED packages, capacitors, and diodes, as well as electronic components such as resin films, printed circuit boards, flexible printed circuit boards, flexible flat cables, rigid flexible boards, glass epoxy boards, and glass boards. The first and second connection target members are preferably electronic components.

[0091] Examples of the electrodes provided on the connection target members include metal electrodes such as gold electrodes, nickel electrodes, tin electrodes, aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, SUS electrodes, and tungsten electrodes. When the connection target members are flexible printed circuit boards, the electrodes are preferably gold electrodes, nickel electrodes, tin electrodes, silver electrodes, or copper electrodes. When the connection target members are glass substrates, the electrodes are preferably aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, or tungsten electrodes. When the electrodes are aluminum electrodes, they may be electrodes made of aluminum only, or may be electrodes in which an aluminum layer is laminated on the surface of a metal oxide layer. Examples of materials for the metal oxide layer include indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element. Examples of the trivalent metal element include Sn, Al, and Ga.

[0092] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0093] Epoxy compounds: Epoxy compound 1 (bisphenol F type epoxy compound, "YDF-8170C" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.) Epoxy compound 2 (bixylenol type epoxy compound, "YX-4000HK" manufactured by Mitsubishi Chemical Corporation)

[0094] Hardener: Acid anhydride hardener 1 (a mixture of hexahydrophthalic anhydride and methylhexahydrophthalic anhydride, "Rikacid MH-700" manufactured by New Japan Chemical Co., Ltd.) Acid anhydride hardener 2 (tetrahydrophthalic anhydride, "Rikacid TH" manufactured by New Japan Chemical Co., Ltd.) Imidazole hardener (Shikoku Chemical Industry Co., Ltd. "2E4MZ-A")

[0095] Organophosphorus compounds: Organic phosphorus compound 1 (tetrabutylphosphonium bromide, "Hishicoline PX-4B" manufactured by Nippon Chemical Industry Co., Ltd., melting point: 110°C) Organic phosphorus compound 2 (methyl tributylphosphonium dimethyl phosphate, "Hishicoline PX-4MP" manufactured by Nippon Chemical Industry Co., Ltd., melting point: 10°C)

[0096] (Examples 1 to 8 and Comparative Examples 1 and 2) (1) Preparation of non-conductive flux or composition The components shown in Tables 1 to 3 below were mixed in the amounts shown in Tables 1 to 3 below to obtain non-conductive fluxes or compositions.

[0097] (2) Fabrication of connection structure The non-conductive flux (composition) immediately after preparation was filled into a dipping tank. A BGA (0.8 mm pitch, 100 electrodes) was prepared as a first connection target member (package) having a first electrode on its surface. A printed circuit board (material: FR4, thickness: 1 mm) having a second electrode (gold electrode) corresponding to the first connection target member on its surface was prepared as a second connection target member. The first connection target member was immersed in a dipping tank for 1 second, and the non-conductive flux (composition) was placed on the solder particles on the surface of the first electrode body (first placement step). Next, the second connection target member was stacked on the lower surface of the non-conductive flux (composition) so that the electrodes face each other (second placement step). The weight of the second connection target member is added to the solder particles and the non-conductive flux (composition). From that state, the solder particles and the non-conductive flux were heated so that the temperature of the solder particles and the non-conductive flux reached the melting point of the solder particles 50 seconds after the start of heating. Furthermore, 65 seconds after the start of the temperature rise, the solder particles (solder portion) and the non-conductive flux (resin portion) were heated to a temperature of 160° C. Thereafter, the temperature was held at 160° C. for 120 seconds to harden the non-conductive flux (composition), thereby obtaining a connection structure. No pressure was applied during heating.

[0098] (evaluation) (1) Viscosity The viscosity (η25) of 0.1 mL of the obtained non-conductive flux (composition) was measured at 25°C and 10 rpm using an E-type viscometer ("TVE22L" manufactured by Toki Sangyo Co., Ltd.) The cone rotor used was 3°×R7.7.

[0099] (2) Adhesive strength The obtained non-conductive flux (composition) was applied to the surface of a stainless steel plate to a thickness of 50 μm to obtain a laminate. Using a tack tester (UBM's "TA-500"), a probe (diameter 8 mm, 10 g) was pressed into the laminate for 10 seconds, and the load when the probe was lifted at a speed of 0.1 mm / second was measured, and this was taken as the adhesive strength at 25°C.

[0100] (3) Impact resistance (drop reliability) The resulting connection structure was dropped 300 times at an acceleration of 1500 G. The number of connection structures that had an open defect among 20 connection structures after the drop test was regarded as the number of failures. The impact resistance was evaluated according to the following criteria.

[0101] [Impact resistance evaluation criteria] XX: 0 failures ○: 1 fault △: 2 faults ×: 3 or more faults

[0102] (4) Suppression of solder flash The obtained connection structure was heated to the melting point of the solder particles 50 seconds after the start of the temperature rise. Furthermore, 75 seconds after the start of the temperature rise, the temperature of the solder part and the resin part was heated to 180°C, and held at 180°C for 60 seconds. After cooling, the number of connection structures that had open defects or short circuits out of 20 connection structures was recorded as the number of open defects or short circuits. The suppression of solder flash generation was evaluated according to the following criteria.

[0103] [Criteria for determining suppression of solder flash occurrence] ○: 0 open defects or short circuits ×: One or more open defects or short circuits

[0104] (5) Conduction reliability (between upper and lower electrodes) For the 20 connection structures obtained, the connection resistance between the upper and lower electrodes was measured at 100 locations using a two-terminal resistance meter, and the average connection resistance was calculated. Note that, based on the relationship of voltage = current x resistance, the connection resistance can be calculated by measuring the voltage when a constant current is passed. The conduction reliability was evaluated according to the following criteria.

[0105] [Criteria for determining continuity reliability] ○: The average connection resistance is 0.9 mΩ or less ×: The average connection resistance exceeds 0.9 mΩ, or a connection failure occurs.

[0106] (6) Dipping properties In the preparation of the above connection structure, the first connection target member was immersed in a dipping bath for 1 second, and then the first connection target member was removed. The amount of non-conductive flux (composition) attached to the solder particles was visually confirmed. The dipping property was evaluated according to the following criteria.

[0107] [Criteria for dipping properties] ○: The first connection target member can be pulled out of the dipping tank, and a sufficient amount of non-conductive flux (composition) can be placed on the surface of the solder particles to fill the gaps between the connection target members. ×: The first member to be connected cannot be pulled up from the dipping tank, or a sufficient amount of non-conductive flux (composition) cannot be placed on the surface of the solder particles to fill the gaps between the members to be connected.

[0108] (7) Flux properties The obtained non-conductive flux (composition) was applied to a thickness of 150 μm on the surface of a gold-plated printed circuit board, and SnBi solder particles (particle diameter 500 μm, melting point 139° C.) were placed on the surface of the composition to obtain a test specimen. The obtained test specimen was heated to 160° C. at 2° C. / sec in a nitrogen atmosphere (oxygen concentration 100 ppm or less) using a reflow simulator (Cores Corporation, “Core9046a”), and then cooled to room temperature (23° C.) after being held for 3 minutes. Thereafter, the shape of the solder that spread out was approximated by an ellipse, and the average of the minor axis and major axis of the ellipse ((minor axis + major axis) / 2) was taken as the solder wet diameter of the non-conductive flux (composition). The flux property was judged according to the following criteria. When the ellipse was a perfect circle, the solder wet diameter of the non-conductive flux (composition) was taken as the diameter of the perfect circle.

[0109] [Fluxability criteria] 〇: Solder wettability diameter is 600μm or more ×: Solder wettability diameter is less than 600 μm

[0110] (8) Non-conductive A non-conductive flux (composition) was applied to a thickness of 100 μm on the surface of a comb-shaped substrate having a copper electrode on the surface to obtain a test specimen. The obtained test specimen was heated to 160° C. at 2° C. / sec in a nitrogen atmosphere (oxygen concentration 100 ppm or less) using a reflow simulator (Cores Corporation, "Core9046a"), and then cooled to room temperature (23° C.). A voltage of 5 V was then applied, and the insulation resistance was measured using a measuring device (ESPEC Corporation, "Electrochemical Migration Evaluation System"). The non-conductivity was evaluated according to the following criteria.

[0111] [Criteria for determining non-conductivity] 〇: Insulation resistance is 1.0×10 6 Ω or more ×: Insulation resistance is 1.0×10 6 Less than Ω

[0112] The results are shown in Tables 1 to 3 below.

[0113] [Table 1]

[0114] [Table 2]

[0115] [Table 3]

[0116] In each of the examples, the reflow process was performed only once. [Explanation of symbols]

[0117] 1...Connection structure 2...First connection target member 2a...First electrode body 2b…Solder particles 2B…Solder part 3...Second connecting member 3a...Second electrode 4…Resin part 4X…Dipping tank 4Xa…Non-conductive flux

Claims

1. A non-conductive flux comprising an epoxy compound, an acid anhydride curing agent, and an organophosphorus compound.

2. Adhesive strength at 25°C is 100,000 N / m 2 More than 210000N / m 2 2. The non-conductive flux of claim 1, wherein:

3. 3. The non-conductive flux according to claim 1, having a viscosity at 25° C. of 400 Pa·s or less.

4. 4. The non-conductive flux according to claim 3, having a viscosity at 25° C. of 50 Pa·s or less.

5. The non-conductive flux according to any one of claims 1 to 4, wherein the content of the organophosphorus compound is 0.5 parts by weight or more and 10 parts by weight or less with respect to 100 parts by weight of the acid anhydride curing agent.

6. The non-conductive flux according to any one of claims 1 to 5, wherein the content of the acid anhydride hardener is 5% by weight or more and 50% by weight or less in 100% by weight of the non-conductive flux.

7. The non-conductive flux according to any one of claims 1 to 6, which is a paste.

8. a first connection target member having a first electrode on a surface thereof; a second connection target member having a second electrode on a surface thereof; a resin portion connecting the first connection target member and the second connection target member, the first electrode comprises a first electrode body and solder particles on a surface of the first electrode body; The first electrode body and the second electrode are electrically connected to each other, A connection structure, wherein the material of the resin portion is the non-conductive flux according to any one of claims 1 to 7.

9. A first connection target member has a first electrode on a surface thereof, the first electrode comprising a first electrode body and solder particles on the surface of the first electrode body, and the first connection target member is provided with the non-conductive flux according to any one of claims 1 to 7. A first arrangement step of arranging the non-conductive flux on the surface of the solder particles of the first connection target member, a second arrangement step of arranging the first connection target member on which the non-conductive flux is arranged and a second connection target member having a second electrode on a surface thereof such that the first electrode and the second electrode face each other; a step of heating the solder particles and the non-conductive flux to electrically connect the first electrode and the second electrode, and forming a resin portion connecting the first connection target member and the second connection target member using the non-conductive flux.

10. The method for manufacturing a connection structure according to claim 9 , wherein in the first placing step, the non-conductive flux is placed by dipping.

Citation Information

Patent Citations

  • Liquid epoxy resin composition and flip-chip semiconductor device

    JP2003183480A

  • Semiconductor chip surface mounting method

    JP2005039206A

  • Non-conductive flux, connection structure, and method for manufacturing connection structure

    JP7592719B2

  • Manufacturing method for semiconductor device and semiconductor device

    WO2009147828A1

  • Semiconductor package substrate, semiconductor package, and semiconductor device

    JP2018186121A